2019
DOI: 10.18517/ijaseit.9.5.9292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Macronutrient Needs on Digestibility and Average Daily Gain of Sheep (Ovisaries var. Padjadjaran, Family Bovidae)

Abstract: Feeding management is a very important factor that makes sure fulfil quality and quantity for livestock nutrient sufficiency that affects the success rate in livestock farming. The excellent macro nutrient needs determination is an absolute thing to achieve the optimal growth which represented by digestibility and average daily gain. Feed formulation that considering the material selection, availability, and the price of feed materials could gave sustainable livestock feed management. The study was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The results of previous studies were also reported that chitosan does not only acts as a stimulator of nutrient absorption but also helps to control and balance the levels of the enzymes SGOT and SGPT because it acts as an antioxidant that increases the process of protein anabolism [33][34][35]. The ability of chitosan as an antioxidant implies that it does not only prevent free radicals as a result of the aflatoxin content of the ration but also acts as an anti-inflammatory.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of previous studies were also reported that chitosan does not only acts as a stimulator of nutrient absorption but also helps to control and balance the levels of the enzymes SGOT and SGPT because it acts as an antioxidant that increases the process of protein anabolism [33][34][35]. The ability of chitosan as an antioxidant implies that it does not only prevent free radicals as a result of the aflatoxin content of the ration but also acts as an anti-inflammatory.…”
Section: Resultsmentioning
confidence: 99%
“…The provision of chitosan in the ration increases the growth of villi as well as digestibility and absorption of nutrients. Feed with the addition of chitosan stimulates immune function and improves digestion and absorption of nutrients to improve growth performance [30][31][32][33]. It is associated with the risk of reducing liver tissue damage, which is characterized by a decrease in the value of SGPT and SGOT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The digestibility of organic matter shows the number of nutrients (fats, carbohydrates, and protein) digested by livestock, while dry matter digestibility indicates levels of food digested by microbes and rumen digestive enzymes. The high percentage of dry digestibility ingredients indicates the higher quality of the feed (Suardin et al, 2014;Hidayat et al, 2019). The digestion value of organic matter (OMD), as well as dry matter digestibility (DMD), are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The productivity is considered better than other types of local chickens in Indonesia [1]. However, livestock productivity is strongly influenced by environmental factors such as the physical environment (temperature, humidity) [2,3] and also feed factors [4][5][6]. The development and environmental maintenance should be pursued simultaneously and in synergy.…”
Section: Introductionmentioning
confidence: 99%